2021
DOI: 10.52324/001c.21211
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Economic Complexity and the Pattern of Foreign Direct Investment Flows among Mexican States

Abstract: Identifying factors that explain the regional distribution patterns of Foreign Direct Investment (FDI) flows into an economy is no simple task, since they depend on a range of factors. In the case of Mexico, previous studies have documented the role of diverse characteristics in attracting FDI to the country's states. This study shows that economic complexity -a variable that indicates the productive capabilities or productive knowledge that exist in a given economy's economic structure -can explain the distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…This is exemplified by the existence of an important "home bias" in manufacturing investment decisions, i.e., a spatial clustering of firms' affiliates that belong to the same industrial group: firms tend to set up new affiliates closed to existing affiliates within the same industrial group (Mayer et al, 2010). These suggest that countries with greater economic complexity are likely to attract higher FDI flows (e.g., Gómez-Zaldívar et al 2021).…”
Section: Theoretical Discussion On the Effect Of Economic Complexity On Services Export Diversificationmentioning
confidence: 99%
“…This is exemplified by the existence of an important "home bias" in manufacturing investment decisions, i.e., a spatial clustering of firms' affiliates that belong to the same industrial group: firms tend to set up new affiliates closed to existing affiliates within the same industrial group (Mayer et al, 2010). These suggest that countries with greater economic complexity are likely to attract higher FDI flows (e.g., Gómez-Zaldívar et al 2021).…”
Section: Theoretical Discussion On the Effect Of Economic Complexity On Services Export Diversificationmentioning
confidence: 99%
“…This is because the ability of people to form social and professional networks plays a critical role in the capacity of a country to produce sophisticated products (e.g., Fukuyama, 1996;Hausmann, 2016;Hidalgo, 2015). Sadeghi et al (2020) and Gómez-Zaldívar et al (2021) have demonstrated empirically[11] that increasingly complex (or sophisticated) economies attract higher FDI in ows. Mayer et al (2010) have established that there exists a signi cant 'home bias' in rms' decisions to engage in manufacturing investment in the host country: rms tend to set up new a liates closed to existing a liates within the same industrial group.…”
Section: Theoretical Discussionmentioning
confidence: 99%
“…Economic complexity has been found as an important determinant of FDI in ows (e.g., Sadeghi et al 2020;Gómez-Zaldívar et al 2021) (see discussion in section 2).…”
Section: Model Speci Cationmentioning
confidence: 99%
“…As noted above, economic complexity signi cantly affects the level of economic complexity, which we have proxied by the real per capita income; hence, the reverse causality from the economic complexity variable to the real per capita income variable. Countries that improve their level of economic complexity can attract FDI in ows (e.g., Gómez-Zaldívar et al 2021) because MNEs may choose to set up plants in countries that manufacture complex products, given the speci c advantages of these countries in terms of productive knowledge and exclusive capabilities. Gómez-Zaldívar et al (2021) and Sadeghi et al (2020) have found evidence that countries with greater economic complexity attract higher FDI ows, while Antonietti and Franco (2021) have uncovered that economic complexity does not (Granger) cause FDI ows to developing countries.…”
Section: Econometric Approachmentioning
confidence: 99%
“…Countries that improve their level of economic complexity can attract FDI in ows (e.g., Gómez-Zaldívar et al 2021) because MNEs may choose to set up plants in countries that manufacture complex products, given the speci c advantages of these countries in terms of productive knowledge and exclusive capabilities. Gómez-Zaldívar et al (2021) and Sadeghi et al (2020) have found evidence that countries with greater economic complexity attract higher FDI ows, while Antonietti and Franco (2021) have uncovered that economic complexity does not (Granger) cause FDI ows to developing countries. In spite of the unconclusive outcomes of the limited existing literature on the effect of economic complexity on FDI in ows, we do consider the variable "FDI" as endogenous in the present analysis.…”
Section: Econometric Approachmentioning
confidence: 99%